Paradox between Supreme Court Decisions and Regulation - Novi Antry (PT FORMOSA CENDEKIA GLOBAL, 2026)
Mortgage execution auctions constitute a cornerstone of Indonesia’s banking credit security system, yet judicial practice reveals a structure paradox between regulations protecting bona fide purchasers and supreme Court decisions that nullify lawfully conducted auctions. This study aimed to analyse the normative legal protection framework, identify the factors underlying the paradox, and formulate a regulatory reconstruction. This study using prescriptive analytical normative legal research with statute, case and conceptual approaches, it examines Supreme Court ruling between 2018 to 2025 through theories of legal certainty, protections and rechtsvinding. The findings expose four interlocking causes of the paradox and recommend elevating auctions finality to statutory ranks, issuing a substantive PERMA, and integrating inter-institutional single system and enforcing judicial restraint to secure consistency between legal norms and judicial practice.